2013
DOI: 10.3171/2013.3.peds12519
|View full text |Cite
|
Sign up to set email alerts
|

Intrasacral meningocele in the pediatric population

Abstract: Object Intrasacral meningoceles are rare cystic lesions that can cause focal compression within the bony sacral canal. Their mechanisms are poorly understood, but most intrasacral meningoceles appear to be intrasacral extradural cysts caused by arachnoid herniating through a small dural defect in the caudal end of the thecal sac. As opposed to perineural cysts, they are not associated with an exiting nerve root. When symptomatic, they can cause sacral pain or sacral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…[37] An extensive review into these lesions was carried out in 1990; this showed that 69% of patients presented with lower back pain and pain in the buttocks and legs. Nearly 56% of these patients had associated weakness in the lower limbs and 44% had altered bowel and bladder habits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[37] An extensive review into these lesions was carried out in 1990; this showed that 69% of patients presented with lower back pain and pain in the buttocks and legs. Nearly 56% of these patients had associated weakness in the lower limbs and 44% had altered bowel and bladder habits.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Surgery is indicated when there are worsening symptoms or when imaging shows an increase in the size of the cyst. [7] Surgery for an intrasacral meningocele is performed if the child has surgery for a related spinal disorder such as cord tethering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients harboring SEACs are asymptomatic and they are often seen as incidental asymptomatic findings in imaging examinations performed for other reasons [17,21]. Indeed, extradural meningeal cysts, especially in the sacrum, seldom cause compressive effects.…”
Section: Clinical Manifestations and Surgical Treatmentmentioning
confidence: 96%
“…The objective of surgery, offered in symptomatic cases of SEAC, is cyst decompression and obliteration of the fistulous communication whenever possible [17]. Other surgical alternatives include cyst resection, incision and drainage, plication of the cyst, lumboperitoneal shunt placement, and simple bone decompression via a sacral laminectomy without manipulating cyst [21].…”
Section: Article In Pressmentioning
confidence: 99%